Being Miss America : behind the rhinestone curtain - Shindle, Kate (Discovering America series., 2014)
In Being Miss America, Kate Shindle interweaves an engrossing, witty memoir of her year as Miss America 1998 with a fascinating and insightful history of the pageant. She explores what it means to take on the mantle of America's "ideal," especially considering the evolution of the American female identity since the pageant's inception. Shindle profiles winners and organization leaders and recounts important moments in the pageant's story, with a special focus on Miss America's iconoclasts, including Bess Myerson (1945), the only Jewish Miss America; Yolande Betbeze (1951), who crusaded against the pageant's pinup image; and Kaye Lani Rae Rafko (1987), a working-class woman from Michigan who wanted to merge her famous title with her work as an oncology nurse. Shindle's own account of her work as an AIDS activist--and finding ways to circumvent the "gown and crown" stereotypes of Miss America in order to talk honestly with high school students about safer sex--illuminates both the challenges and the opportunities that keep young women competing to become Miss America